Gastric Trichobezoar with Outlet Obstruction in a Child of 4 Years old - A Rare Occurrence (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v34i1.5699Bangladesh Journal of Child Health 2010; Vol.34(1): 25-27